Isocitrate dehydrogenase inhibitors in acute myeloid leukemia - Xiaoyan Liu; Yuping Gong (BMC, 2019)
Abstract Isocitrate dehydrogenase (IDH) is a key enzyme involved in the conversion of isocitrate to α-ketoglutarate (α-KG) in the tricarboxylic acid (TCA) cycle. IDH mutation produces a neomorphic enzyme, which can lead to the abnormal accumulation of R-2-HG and promotes leukemogenesis. IDH mutation occurs in 20% of acute myeloid leukemia (AML) patients, mainly including IDH1 R132, IDH2 R140, and IDH2 R172. Different mutant isoforms have different prognostic values. In recent years, IDH inhibitors have shown good clinical response in AML patients. Hence, enasidenib and ivosidenib, the IDH2 and IDH1 inhibitors developed by Agios Pharmaceuticals, have been approved by the Food and Drug Administration on 1 August 2017 and 20 July 2018 for the treatment of adult relapsed or refractory (R/R) AML with IDH2 and IDH1 mutations, respectively. IDH inhibitor monotherapy for R/R AML is efficacious and safe; however, there are problems, such as primary or acquired resistance. Clinical trials of IDH inhibitors combined with hypomethylating agents or standard chemotherapy for the treatment of R/R AML or newly diagnosed AML, as well as in post hematopoietic stem cell transplantation as maintenance therapy, are ongoing. This article summarizes the use of IDH inhibitors in AML with IDH mutations.